"If we're wrong, take us to court": an analysis of special police services (SPS) arrangements for the policing of football in England and Wales - Hester, Richard (International journal of law, crime and justice, 2024)
Under the Police Act 1996, Special Police Services (SPS) allow the police in England and Wales to partially cost recover for resources deployed to police events such as football, horse racing and music festivals. Historically, there have been numerous legal cases about SPS charges involving police forces and event organisers. Most recently Ipswich Town Football Club Company Limited vs. The Chief Constable of Suffolk Constabulary [2017] EWCA Civ 1484, resulted in clarification on points of law and a more restricted area within which police forces can charge for SPS. This qualitative research interviews police officers engaged in policing football, football club representatives and other key stakeholders involved in the SPS negotiation process. It finds that there are divisive approaches by both parties, which can result in compromising public safety. The notion of SPS being abolished is explored, despite potential benefits of this, further research is recommended to examine this further.